Management of pencak silat achievement in IPSI Klaten Regency in 2015-2019 - Krisnanda Ramadhan; Singgih Hendarto; Budhi Satyawan (PJKR FKOR UNS, 2020)
This study aims to find out the organizational, recruitment, and training management of pencak silat coaching in IPSI Klaten Regency. This study was carried out at the pencak silat hermitage, Klaten Regency, using qualitative-descriptive method. The analysis unit was IPSI Klaten Regency. Data collection techniques included documentation, in-depth interview, and observation. The data were obtained from the management, coaches, and athletes of pencak silat coaching in IPSI Klaten Regency. It was found that (1) in the organizational management of pencak silat coaching in Klaten Regency, fairly good cooperation between the management and the coaches and athletes have been established; (2) the recruitment implementation has been good enough with the invitation of participants from each pencak silat school by giving a circular letter for the IPSI management to participate in several stages of selection; (3) the training management is carried out by providing a training program planning with the coordination of the management and the coach according to the athlete's needs; the planned training program can be developed according to circumstances and needs of the athlete. Therefore, based on the data analysis, it is concluded that the management of pencak silat coaching in IPSI Klaten Regency has been running quite well, but there is still a weakness. In athlete recruitment, some IPSI schools have not sent their athletes to take part in the selection yet. This needs to be solved, and IPSI Klaten Regency should always make improvements in their management for a better performance.